Research designs for language studies - Othman, Juliana (University of Malaya Press, 2019)
Research Designs for Language Studies is a comprehensive resource book in research methodology in the field of applied language studies. It is designed to introduce novice researchers to available methods for language-related investigations and assist them in identifying the best designs for the studies that they are planning. The book consists of nine chapters, covering a wide range of research methods in different areas of language education and applied linguistics. Each chapter provides step-by-step procedure in administering each design with specific references made to reported studies. Examples are drawn from actual research in illustrating data collection and data analysis while the choice of analyses is also included.